ANALISIS BEBAN KOGNITIF SISWA PADA KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DALAM POKOK BAHASAN PERBANDINGAN - Avianti Permata Yuniar; Aan Hendrayana; Yani Setiani (TIRTAMATH: Jurnal Penelitian dan Pengajaran Matematika, 2019)
This study was aimed to know cognitive load that arise in students when show theirs mathematical problem solving ability to solve about comparison topic. This study used descriptive study methods because the issue raised is not yet clear, holistic, complex, dynamic and full of meaning, so that the data may not be captured by quantitative research methods. While the instrument used is the Test of problem solving ability with Polya’s steps, observation and interviews. The results of this study proved that the mathematical problem solving abilities are supported by their high germane cognitive load is high, whereas the intrinsic and extrinsic cognitive load is not too obtrusive.